Changes in Functional Health, Changes in Medication Beliefs, and Medication Adherence - Schüz, Benjamin; Wurm, Susanne; Ziegelmann, Jochen P.; Warner, Lisa Marie; Tesch-Römer, Clemens; Schwarzer, Ralf (Health psychology, 2011)
Objective: Medication adherence often lies below recommendations although it is crucial for effective therapies, particularly in older adults with multiple illnesses. Medication beliefs are important factors for individual adherence, but little is known about their origin. We examine whether changes in functional health predict changes in medication beliefs, and whether such changes in beliefs predict subsequent medication adherence. Design: At three points in time over a 6-month period, 309 older adults (65-85 years) with multiple illnesses were assessed. Latent true change modeling was used to explore changes in functional health and medication beliefs. Adherence was regressed on changes in beliefs. Main Outcome Measures: Medication beliefs were measured by the Beliefs About Medicines Questionnaire; medication adherence by the Reported Adherence to Medication Scale. Results: Functional health and medication beliefs changed over time. Increasing physical limitations predicted increases in specific necessity and specific concern beliefs, but not in general beliefs. Changes in specific necessity beliefs predicted intentional adherence lapses, changes in general overuse beliefs predicted unintentional adherence lapses. Conclusions: Medication beliefs partly depend on health-related changes, and changes in beliefs affect individual adherence, suggesting to target such beliefs in interventions and to support older adults in interpreting health changes. © 2011 American Psychological Association.
Keywords: Functional health; Medication adherence; Medication beliefs; Older adults; Symptoms